2016
DOI: 10.1016/j.bbagen.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy is not uniformly cytoprotective: a personalized medicine approach for autophagy inhibition as a therapeutic strategy in non-small cell lung cancer

Abstract: BACKGROUND Lung cancer is the leading cause of cancer-related death worldwide. In addition to surgical resection, which is considered first-line treatment at early stages of the disease, chemotherapy and radiation are widely used when the disease is advanced. Of multiple responses that may occur in the tumor cells in response to cancer therapy, the functional importance of autophagy remains equivocal; this is likely to restrict current efforts to sensitize this malignancy to chemotherapy and/or radiation by ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 99 publications
3
15
0
Order By: Relevance
“…In fact, the effectiveness of targeted therapies for cancers is extremely context dependent. For example, the complexity of the role of autophagy in therapeutic responses to therapy in NSCLC has been demonstrated . Furthermore, recent data demonstrated that cytosolic HSP90 and TRAP1 modulate growth and lung metastasis in vivo, although they do not play any role in the initiation of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the effectiveness of targeted therapies for cancers is extremely context dependent. For example, the complexity of the role of autophagy in therapeutic responses to therapy in NSCLC has been demonstrated . Furthermore, recent data demonstrated that cytosolic HSP90 and TRAP1 modulate growth and lung metastasis in vivo, although they do not play any role in the initiation of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…While radiation-induced autophagy often serves as a protective function in cell culture-based studies, it is still unclear to what an extent autophagy may be induced by radiation in human cancer cells, although the function of autophagy in response to radiation is inconsistent. 23 Some studies reported that autophagy promoted the anticancer effects of radiotherapy; others showed that upregulation of autophagy were associated with tumor resistance in radiation therapy and that blockade of autophagy contributed to the radiosensitization. 24 More recent reports suggested that inhibition of autophagy led to an increased expression of IL1B and IL6 and that autophagy played an important role in tissue inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…CMA is considered to be very selective whereas micro‐autophagy and macro‐autophagy may be selective or non‐selective . In the context of cancer, different forms of autophagy have been identified and have been classified as either cytoprotective, cytotoxic, cytostatic, or non‐protective . This classification applies primarily to the case of autophagy induced in tumor cells in response to therapy whereas basal autophagy is virtually always cytoprotective.…”
Section: Introductionmentioning
confidence: 99%